Sexual Dysfunction in Women with Diabetic Kidney - Ersilia Satta; Carlo Magno; Alessandro Galì; Antonino Inferrera; Roberta Granese; Carmela Aloisi; Michele Buemi; Guido Bellinghieri; Domenico Santoro (International Journal of Endocrinology)
Few studies address alteration of sexual function in women with diabetes and chronic kidney disease (CKD). Quality of life surveys suggest that discussion of sexual function and other reproductive issues are of psychosocial assessment and that education on sexual function in the setting of chronic diseases such as diabetes and CKD is widely needed. Pharmacologic therapy with estrogen/progesterone and androgens along with glycemic control, correction of anemia, ensuring adequate dialysis delivery, and treatment of underlying depression are important. Changes in lifestyle such as smoking cessation, strength training, and aerobic exercises may decrease depression, enhance body image, and have positive impacts on sexuality. Many hormonal abnormalities which occur in women with diabetes and CKD who suffer from chronic anovulation and lack of progesterone secretion may be treated with oral progesterone at the end of each menstrual cycle to restore menstrual cycles. Hypoactive sexual desire disorder (HSDD) is the most common sexual problem reported by women with diabetes and CKD. Sexual function can be assessed in women, using the 9-item Female Sexual Function Index, questionnaire, or 19 items. It is important for nephrologists and physicians to incorporate assessment of sexual function into the routine evaluation protocols.